Noções de programação estruturada em Python no ensino de Física: um caminho para o ensino médio por meio da cultura lúdica - Parizotto, Giovanna Moreno (2017)
In this qualitative research with case study elements, we discuss why the use of notions of structured programming in Python language constituted as a manipulation of the play culture for the teaching of Physics in the first year of the High School, at night. Manipulation in this case, refers us to aspects related to notions of game and characteristics related to the game, recognizing the game as a place of emergency of the ludic culture. This theme is related to the teacher training of the researcher, who seeks to enrich the student's playful culture in which she has greater didactic difficulty. In the course of the research, the researchers find several characteristics of the games during the interventions. This process is discussed as to the characteristics of the philosophical game proposed by Brougère (1998) and also to the typical behaviors of them, considered as primary impulses by Caillois (1990), related to the term game. We also relate corruption characteristics of these primary impulses to the lubricant ludic term.